MEI A Level Further Mathematics Year 2 4th Edition. - Baldwin, Claire (Hodder Education Group, 2017)
Exam Board: MEILevel: A-levelSubject: MathematicsFirst Teaching: September 2018First Exam: June 2019 Help students to develop their knowledge and apply their reasoning to mathematical problems with textbooks that draw on the well-known MEI (Mathematics in Education and Industry) series, updated and tailored to the 2017 OCR (MEI) specification and developed by subject experts and MEI.- Ensure targeted development of reasoning and problem-solving skills with plenty of practice questions and structured exercises that build mathematical skills and techniques.- Build connections between topics, u.